2017
DOI: 10.1186/s13047-017-0206-5
|View full text |Cite
|
Sign up to set email alerts
|

The comparative efficacy of angiosome‐directed and indirect revascularisation strategies to aid healing of chronic foot wounds in patients with co‐morbid diabetes mellitus and critical limb ischaemia: a literature review

Abstract: BackgroundIschaemic ulcerations have been reported to persist and/or deteriorate despite technically successful revascularisations; a higher incidence of which affects patients with diabetes and critical limb ischaemia. In the context of wound healing, it is unclear if applications of the angiosome concept in ‘direct revascularisation’ (DR) would be able to aid the healing of chronic foot ulcerations better than the current ‘best vessel’ or ‘indirect revascularisation’ (IR) strategy in patients with co-morbid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 77 publications
(146 reference statements)
1
14
0
Order By: Relevance
“…A recent retrospective study of endovascular limb salvage attempts in patients with DFU suggested that indirect angiosome revascularization was associated with poorer outcomes than direct revascularization . However, because of lack of clear definitions and factors like selection bias, the effectiveness of the angiosome concept in patients with diabetes is unknown . Particularly in patients with diabetes who usually have poor collaterals, restoration of flow to an artery directly supplying the affected area seems the best approach during an endovascular procedure .…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective study of endovascular limb salvage attempts in patients with DFU suggested that indirect angiosome revascularization was associated with poorer outcomes than direct revascularization . However, because of lack of clear definitions and factors like selection bias, the effectiveness of the angiosome concept in patients with diabetes is unknown . Particularly in patients with diabetes who usually have poor collaterals, restoration of flow to an artery directly supplying the affected area seems the best approach during an endovascular procedure .…”
Section: Treatmentmentioning
confidence: 99%
“…57 However, because of lack of clear definitions and factors like selection bias, the effectiveness of the angiosome concept in patients with diabetes is unknown. 55,[58][59][60] Particularly in patients with diabetes who usually have poor collaterals, restoration of flow to an artery directly supplying the affected area seems the best approach during an endovascular procedure. 56 Successfully opening one or more occluded vessels is not the same as a clinically successful procedure and before the procedure is terminated blood flow to the ulcer area should therefore be assessed.…”
Section: Rationalementioning
confidence: 99%
“…Regarding angiosome revascularisation, many studies of endovascular and open approaches have yielded results both in favour of 7e12 and against 3,13,14 the procedure. In a recent meta-analysis and systematic review, 15,16 it was suggested, despite reservations about low quality data and insufficient power for a definitive recommendation, that directed revascularisation (angiosome) could be associated with better wound healing and limb salvage. 15,16 In the recent 2017 ESC (European Society of Cardiology) Guideline in collaboration with the ESVS (European Society for Vascular Surgery), the direct strategy was recommended if the artery was accessible and open to the foot.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent meta-analysis and systematic review, 15,16 it was suggested, despite reservations about low quality data and insufficient power for a definitive recommendation, that directed revascularisation (angiosome) could be associated with better wound healing and limb salvage. 15,16 In the recent 2017 ESC (European Society of Cardiology) Guideline in collaboration with the ESVS (European Society for Vascular Surgery), the direct strategy was recommended if the artery was accessible and open to the foot. 17 So, in many cases, considering the technical aspects of the diagnostic angiogram, the easiest artery to recanalise is treated instead of following the angiosome directed strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study of 70 diabetic patients, Jeon et al 37 observed a significant difference in healing (87% vs 47%, p<0.05) in the direct revascularization or angiosome-oriented subgroup vs IR interventions. Similarly, Khor et al 36 reviewed the literature on 280 diabetic subjects with critical limb ischemia treated by direct vs indirect revascularization strategy, finding not only better wound healing outcomes but also a nearly 2-fold increase in the probability of wound healing within 12 months (HR 1.97, 95% CI 1.34 to 2.90) for direct revascularization.…”
Section: Discussionmentioning
confidence: 96%